ZIF-67/g-C3N4-Modified Electrode for Simultaneous Voltammetric Determination of Uric Acid and Acetaminophen with Cetyltrimethylammonium Bromide as Discriminating Agent. (27th January 2020) - Ngo, Huynh Truong; Hoa, Le Thi; Khanh, Nguyen Tan; Hoa, Tran Thi Bich; Toan, Tran Thanh Tam; Mau, Tran Xuan; Phong, Nguyen Hai; Thang, Ho Sy; Khieu, Dinh Quang
Abstract : In the present paper, the ZIF-67/ g -C3 N4 composite was synthesized and utilized as a modifier for a glassy carbon electrode for the simultaneous voltammetric determination of uric acid (URA) and acetaminophen (ACE) with cetyltrimethylammonium bromide (CTAB) as a discriminating agent. The composite was characterized using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and nitrogen adsorption/desorption isotherms. The obtained ZIF-67/ g -C3 N4 composite exhibits good textural properties (specific surface area: 75 m 2 ·g −1 ) and is stable in water with a pH range of 3 to 10. The ZIF-67/ g -C3 N4 -modified electrode combined with CTAB as a discriminating agent possesses excellent catalytic electrochemistry towards URA and ACE with well-defined electrochemical responses. The electrochemical kinetics study is also addressed. The linear relation of the oxidation peak current of URA and ACE and the concentration ranging from 0.2  μ M to 6.5  μ M provide a detection limit of 0.052  μ M for URA and 0.053  μ M for ACE. The proposed method is well-suited to simultaneously analyze URA and ACE in human urine with comparable results with HPLC.